International experience in personal data protection (2020)
The article is devoted to the analysis of various approaches to the protection of personal data in Russia and the European Union. In order to determine the importance of observing the right to protection of personal data, a number of documents of the European Commission adopted over the past few years have been analyzed. General scientific and special legal methods of cognition allowed for a comparative analysis of Regulation 2016/679 on the Protection of Individuals in the Processing of Personal Data and Their Free Movement (2018) and EU Directive 2016/680. Although Russia has ratified the Council of Europe Convention for the Protection of Individuals with regard to Automatic Processing of Personal Data (1981), it has not been able to solve a number of problems related to the mandatory notification about personal data leaks, protection of personal data during their processing and against unauthorized access, etc. As a result, conclusions are drawn regarding the prevailing approaches to the definition of personal data and a unified conceptual and categorical apparatus in the field of personal data. Proposals for the modernization of Russian legislation based on international experience are made as well.